Analisis Pemikiran Islam Kontemporer: (Kajian Kritis terhadap Pemikiran Harun Nasution) - Abbas, Nurlaelah; Rachman, M. Aditya (Jurnal Publisitas, 2023)
The paper examines Harun Nasution's perspectives on Islamic contemporary thought, emphasizing the distinction between foundational (qath’i) and non-foundational (dhanni) aspects. Nasution advocated for differentiating absolute and relative teachings for Islamic reform. His work delved into the roles of reason (aql) and revelation (wahyu), citing Quranic verses promoting rational thinking. Nasution also critiqued the Mu'tazilah thought, appreciating its emphasis on reason but noting a lack of tolerance.As a modern thinker, Nasution integrated values from Dutch education and studied in Saudi Arabia, Egypt, and Canada. The research focuses on Nasution's book "Islam Rasional: Gagasan dan Pemikiran," using qualitative analysis to explore various aspects of Islamic thought, the role of reason, and differences among Islamic thinkers. Harun Nasution emphasized the significance of distinguishing between fundamental (qath’i) and non-fundamental (dhanni) tenets in Islam. He marked the non-fundamental teachings as essential for reform, as opposed to the unalterable nature of fundamental teachings. Additionally, Nasution argued for the harmony between reason (aql) and revelation (wahyu), contending that they need not be in conflict. He has drawn on Quranic verses encouraging philosophical reflection, positing philosophy as a necessity within Islam.